Frequency of CCR5-Δ32, CCR2-64I and SDF1-3'A alleles in HIV-infected and uninfected patients in Istanbul, Turkey - Muammer Osman Köksal; Baki Akgül; Hayati Beka; Sevgi Çiftçi; Fahriye Keskin; Haluk Eraksoy; Ali Ağaçfidan (Journal of Infection in Developing Countries)
Introduction: Co-receptors involved in cell entry of the human immunodeficiency virus (HIV) and mutations in genes encoding their ligands may play a role in the susceptibility to infection and resistance to the progression of the infection. The best studied mutations that can exist in these genes are the CCR5-Δ32, CCR2-64I and SDF1-3'A mutations. The frequency of these mutations vary from continent to continent and even from region to region. However, there is limited information on their distribution throughout the Turkish population. Istanbul is the city with the highest number of documented HIV-infected patients in Turkey, which can be attributed to the population size. The aim of this study was to determine the distribution of three AIDS-related gene variants among HIV-infected and uninfected population in Istanbul, Turkey and to estimate the contribution of these variants to susceptibility or resistance to HIV.